Reforming the Urban Transport Sector in the Rio de Janeiro Metropolitan Region : a case study in concessions - Rebelo, Jorge M. (Policy research working paper, 1999)
April 1999 - In a bold effort to privatize Rio de Janeiro's urban transport sector, the state government showed that political decisiveness, transparency, and ingenuity in developing incentives are crucial to make loss-making operations attractive to the private sector. It also learned that not having a credible staff redundancy program might seriously undermine the benefits expected from concessions. Rebelo describes a bold effort by the state government to increase private sector participation in Rio de Janeiro's urban transport sector, reduce heavy operating subsidies, and establish a foundation for making the sector sustainable. This effort was undertaken with the help of three World Bank-financed loans: ° The Rio de Janeiro Metropolitan Transport loan, which provided assistance for the transfer of federally owned suburban railways to the state government. ° The Rio de Janeiro State Reform and Privatization Loan, which helped the state privatize and grant concessions for a number of its enterprises. ° The Rio de Janeiro Mass Transit Loan, which supported the reorganization of the sector and the concession of the Rio suburban railways (Flumitrens). Most of the reforms in the urban transport sector have been implemented. The lessons learned from implementation and the results obtained so far suggest that political decisiveness, transparency, and ingenuity in developing incentives are crucial to privatizing urban rail transport systems. But the state also learned that not having a credible staff redundancy program might seriously reduce the benefits expected from concessions. This paper-a product of the Transport and Urban Unit, Finance, Private Sector, and Infrastructure Department, Latin America and the Caribbean Region-is part of a larger effort in the region to help borrowers concession loss-making urban transport operations to the private sector.